Tephra correlations and climatic events between the MIS6/5 transition and the beginning of MIS3 in Theopetra Cave, central Greece. (15th June 2015) - Karkanas, Panagiotis; White, Dustin; Lane, Christine S.; Stringer, Chris; Davies, William; Cullen, Victoria L.; Smith, Victoria C.; Ntinou, Maria; Tsartsidou, Georgia; Kyparissi-Apostolika, Nina
Abstract: Three cryptotephra layers associated with important periods of climatic change were identified in the Middle Palaeolithic sequence of Theopetra Cave, Greece. The lower cryptotephra layer, THP-TII5, is correlated with the P-11 Pantellerian eruption dated to ∼128–131 ka. This cryptotephra postdates a thick sequence of combustion layers that show a complex vegetation succession quite similar to that of the last deglaciation succession in the cave. Two other cryptotephras, THP-TII10 and THP-TII12, are correlated with the Nisyros Upper Pumice and the Pantellerian Y6/Green Tuff, dated to >50 ka and 45.7 ka, respectively. This sequence confirms the position of the Nisyros Upper tephra, below the Pantellerian Green Tuff, in the volcanic event stratigraphy of the Mediterranean. Moreover, these two upper cryptotephras bracket an extended combustion layer with interstadial vegetation characteristics that may be coincident with the complex Greenland Interstadial 13–14. On the basis of this new chronology it can be deduced that the intensity of occupation and presence or absence of humans in the cave were closely related to climatic changes. In addition, a remarkable similarity in the pattern of occupational intensity during the last two deglaciations can be suggested. Highlights: Three cryptotephra layers associated with important periods of climatic change in Theopetra Cave. The P-11 Pantellerian caps thick combustion layers formed at the transition of MIS6/5e. Position of the Nisyros Upper tephra is below the Pantellerian Green Tuff. Occupation intensity and presence or absence of humans related to climatic changes. Parallels in the pattern of human occupation during the two last deglaciations.